PERSEPSI ATLET PETANQUE TERHADAP EFEKTIVITAS PROGRAM LATIHAN DL PETANQUE KLUB MATARAM - Musa Zakaria, Muhamad; Ali Muhaimin; Supriadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the perception of athletes on the effectiveness of the training program at DL Petanque Club Mataram. The research uses a quantitative approach with a descriptive type of research. The method used is a survey through the distribution of questionnaires to respondents. The population in this study is all athletes who actively participate in the training program at DL Petanque Club Mataram which totals 22 athletes. The sampling technique uses total sampling so that the entire population is used as a research sample. The research instrument is in the form of a questionnaire with a Likert scale that has been validated by two validators. The data were analyzed using quantitative descriptive techniques by calculating scores and percentages to determine the categories of effectiveness of the exercise program. The results of the study showed that the athletes' perception of the effectiveness of the training program at DL Petanque Club Mataram as a whole was in the effective category. This is shown by the percentage results on each indicator, namely training objectives (68.41%), training materials (74.85%), training methods (69.09%), training intensity (76.82%), role of coaches (73.03%), training facilities (70.30%), evaluation system (73.18%), motivation (72.50%), and mental readiness (74.77%). These results show that the training program implemented has been able to support the improvement of technical skills, physical condition, motivation, and mental readiness of athletes. Based on these findings, it can be concluded that the training program at DL Petanque Club Mataram has run well and is able to make a positive contribution to the athlete coaching process. However, the evaluation and development of training programs still need to be carried out on an ongoing basis so that the quality of training can continue to improve and support the achievement of athletes' achievements optimally.